Round bale alfalfa processing method affects heifer growth but does not influence wastage or eating preference - Jones, S.Q.; Marston, T.T.; Kraus, T.J.; DeRouchey, Joel M.; Waggoner, Justin W.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Many factors affect forage quality, including moisture level at baling, compaction, bulk density, and maturity at harvest. Losses of dry matter and nutrient value occur during field curing. Hay baled at or above 18% moisture should have less nutrient loss in the field. However, hay baled at these moisture levels has the potential to heat during storage, causing dry matter loss and nutrient degradation. Also, as particle length of forage decreases, packing ability of forage and bulk density of bales increase. Although particle length is reduced by grinding baled forage, this can result in nutrient losses. Also, when cattle are fed free choice in a ring feeder, precutting forage may help reduce waste because the smaller particles fall within the ring and are not pulled out by the animals and lost on the ground. Objectives of these experiments were to compare the effects of precutting alfalfa during round baling and conventional baling on heifer performance, forage wastage, and eating preference.
Keywords: Beef; Alfalfa; Heifer; Growth; Performance